New Insight on Medieval Painting in Sicily: The Virgin Hodegetria Panel in Monreale Cathedral (Palermo, Italy) - Maria Letizia Amadori; Valeria Mengacci; Mauro Sebastianelli; Bruno Pignataro; Simonpietro Agnello; Paolo Triolo; Claudia Pellerito (Heritage, 2023)
The Virgin Hodegetria, located in the Cathedral of Santa Maria Nuova in Monreale, near Palermo (Italy), probably dating the first half of the 13th century, is one of the earliest examples of medieval panel painting in Sicily. A diagnostic campaign was carried out on the panel aiming to identify the constituting materials and the executive technique, as well as to assess the state of conservation for supporting the methodological choice of the restoration intervention. Both non-invasive (X-ray radiography, digital microscope, multispectral imaging, ED-X-ray fluorescence) and micro-invasive (polarised light microscopy, ESEM-EDX, ATR-FTIR spectroscopy and micro-Raman spectroscopy) analyses were performed. According to the results, the executive technique followed the 13th–14th-century Italian painting tradition. A complex structure was applied on the wooden support, consisting of a double layer of canvas and several ground layers of gypsum and glue-based binder. The underdrawing was made by a brush using carbonaceous black pigment. The original palette includes red ochre, red lead, azurite, carbon black and bone black. During the several restorations, mercury-based red, indigo, smalt blue, orpiment and synthetic mars were used. The original silver leaf of the frame was covered with red tin-based lake and subsequently regilded with gold leaf. Proteinaceous and oil binders were also detected.